Cabildos de naturales en el ocaso colonial: jurisdicción, posesión y defensa del espacio étnico - Dueñas, Alcira (2016)
This essay examines important changes in the jurisdiction of the Republic of the Indians in late colonial Peru by problematizing the concept of possession and usufruct of communal lands in the Indian towns after 1777, when the Bourbon set the sub-delegate courts to replace the former court of the corregidor. The 1784 and 1803 Ordenanzas de Intendencia displaced more firmly the jurisdictional authority of the indigenous Cabildo and its ability to influence the organization of the town’s spatial order. The indigenous Cabildos’ legal advocates and judges waged in court a systematic defense of communal property and created a new sense of community in the urban setting. At the dawn of the nineteenth century, a rather sophisticated lettered culture anchored in the jurisdictional potential of the republic of the Indians and with a long tradition of legal struggles and legal writing revealed itself. Defying the legal authority of the sub-delegate, the council offered a tacit response to the Bourbon project of political control of the pueblos, in an effort to salvage the last vestiges of community that still remained in the Lima valley’s towns at the end of the colonial experience.